Child Care Arrangements Of Working Mothers - Singh H; Raizada N; Soni R K; Gill P J S (Wolters Kluwer Medknow Publications, 1993)
Children arrangements for infants and preschool children and the reasons for working outside the home were studied in 300 mothers of whom 100 were teachers (Group. I) 100 clerks (groups II) and 100 tabourers (Group III). The interview method was used. The most common (80%) reason for working was financial needs, the next most frequent was utilization of specialized skills. In 58.7% of the cases, substitute childcare was provided by one of the family members, usually the grandmother. Sixty six percent of caretakers were illiterate. Most (93%) of the working mothers had also to perform certain household chores. Bottle-feeding was stated at birth by 80% of these mothers: Childcare arrangements for children of working mothers must be considered in the future.